Identifikasi Waste Melalui Pendekatan Lean Logistics Pada Aktivitas Distribusi Material PT XYZ - Fauzan, Mochamad Patra Bani; Rohendi, Dedi; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Inefficient material distribution at PT XYZ causes production delays in tactical vehicles and increases operational costs. This study aims to identify waste in the material distribution process using the Lean Logistics approach with the help of Value Stream Mapping (VSM) and Process Activity Mapping (PAM) tools. The analysis shows that out of a total distribution time of 6,835 minutes, only 273 minutes (4%) are value-added (VA) activities, while the remainder consists of non-value added (NVA) and necessary non-value added (NNVA) activities. These findings highlight the dominance of wasted time due to delays, transportation, and inefficient storage. The study recommends continuous improvement through lean tools and the implementation of digital technologies to accelerate distribution flow and reduce waste. This approach can enhance overall logistics efficiency and company productivity.